Gains from wage flexibility and the zero lower bound - Roberto Billi; Jordi Galí (Sveriges Riksbank, 2019)
We analyze the welfare impact of greater wage flexibility while taking into account explicitly the existence of the zero lower bound (ZLB) constraint on the nominal interest rate. We show that the ZLB constraint generally amplifies the adverse effects of greater wage flexibility on welfare when the central bank follows a conventional Taylor rule. When demand shocks are the driving force, the presence of the ZLB implies that an increase in wage flexibility reduces welfare even under the optimal monetary policy with commitment.
Keywords: E24; E32; E52; 330; labor market flexibility; nominal rigidities; optimal monetary policy with commitment; Taylor rule; ZLB